2013
DOI: 10.1038/hdy.2013.61
|View full text |Cite
|
Sign up to set email alerts
|

Postzygotic isolation involves strong mitochondrial and sex-specific effects in Tigriopus californicus, a species lacking heteromorphic sex chromosomes

Abstract: Detailed studies of the genetics of speciation have focused on a few model systems, particularly Drosophila. The copepod Tigriopus californicus offers an alternative that differs from standard animal models in that it lacks heteromorphic chromosomes (instead, sex determination is polygenic) and has reduced opportunities for sexual conflict, because females mate only once. Quantitative trait loci (QTL) mapping was conducted on reciprocal F 2 hybrids between two strongly differentiated populations, using a satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(79 citation statements)
references
References 41 publications
6
69
1
Order By: Relevance
“…For example, the number, magnitude, and properties of digenic and trigenic interactions clarifies aspects of speciation theory in evolutionary biology (36, 37). Hybrids between species exhibit reduced fitness, which is usually attributed to negative (‘epistatic’) interactions among genes that diverged in isolated populations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the number, magnitude, and properties of digenic and trigenic interactions clarifies aspects of speciation theory in evolutionary biology (36, 37). Hybrids between species exhibit reduced fitness, which is usually attributed to negative (‘epistatic’) interactions among genes that diverged in isolated populations.…”
Section: Discussionmentioning
confidence: 99%
“…Although DM incompatibilities were originally linked to interactions between nuclear genes, miscommunication between nuclear and mitochondrial genomes has been implicated in yeast (Lee et al, 2008), drosophila and other insects (Dickman and Moehring, 2013; Foley et al, 2013), fish (Bolnick et al, 2008; Niehuis et al, 2008) and in primate xenomitochondrial cybrid cell lines (Bayona-Bafaluy et al, 2005). Previous studies in drosophila found male-specific infertility associated with mitochondrial polymorphism (Clancy et al, 2011; Innocenti et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…(2005). Situations in which polygenic sex determination mediated by mtDNA effects could generate striking changes in sex ratio among distinct hybrid crosses have just begun to be explored in T. californicus (Alexander et al., 2015; Foley, Rose, Rundle, Leong, & Edmands, 2013) and in freshwater fish species ( Cottus sp . ; Cheng, Czypionka, & Nolte, 2013).…”
Section: Discussionmentioning
confidence: 99%